Finding Resolution for the Responsible Transparency of Economic Models in Health and Medicine. - Padula, William V.; McQueen, Robert Brett; Pronovost, Peter J. (Medical Care, 2017)
The Second Panel on Cost-Effectiveness in Health and Medicine recommendations for conduct, methodological practices, and reporting of cost-effectiveness analyses has a number of questions unanswered with respect to the implementation of transparent, open source code interface for economic models. The possibility of making economic model source code could be positive and progressive for the field; however, several unintended consequences of this system should be first considered before complete implementation of this model. First, there is the concern regarding intellectual property rights that modelers have to their analyses. Second, the open source code could make analyses more accessible to inexperienced modelers, leading to inaccurate or misinterpreted results. We propose several resolutions to these concerns. The field should establish a licensing system of open source code such that the model originators maintain control of the code use and grant permissions to other investigators who wish to use it. The field should also be more forthcoming towards the teaching of cost-effectiveness analysis in medical and health services education so that providers and other professionals are familiar with economic modeling and able to conduct analyses with open source code. These types of unintended consequences need to be fully considered before the field's preparedness to move forward into an era of model transparency with open source code.